2013
DOI: 10.1002/nbm.2928
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional mapping of the creatine kinase enzyme reaction rate in muscles of the lower leg

Abstract: Phosphorous (31P) magnetization transfer (MT) techniques enable the non-invasive measurement of metabolic turnover rates of important enzyme catalyzed reactions, such as the creatine kinase reaction (CK), a major transducing reaction involving adenosine triphosphate and phosphocreatine. Alteration in the kinetics of the CK reaction rate appears to play a central role in many disease states. In this study, we developed and implemented at ultra-high field (7T), a novel three-dimensional 31P-MT imaging sequence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 47 publications
4
17
0
Order By: Relevance
“…Our data show that the measurements with the DRESS‐localized FAST method in the gastrocnemius muscle are feasible at 7 T, even without the use of adiabatic excitation pulses. The measured k values for PCr‐to‐ATP ( k CK = 0.26 ± 0.05 s −1 ) and P i ‐to‐ATP ( k ATP = 0.11 ± 0.05 s −1 ) reactions are in good agreement with previously published results of localized experiments . Bottomley et al reported a k CK for localized FAST of 0.29 ± 0.07 s −1 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our data show that the measurements with the DRESS‐localized FAST method in the gastrocnemius muscle are feasible at 7 T, even without the use of adiabatic excitation pulses. The measured k values for PCr‐to‐ATP ( k CK = 0.26 ± 0.05 s −1 ) and P i ‐to‐ATP ( k ATP = 0.11 ± 0.05 s −1 ) reactions are in good agreement with previously published results of localized experiments . Bottomley et al reported a k CK for localized FAST of 0.29 ± 0.07 s −1 .…”
Section: Discussionsupporting
confidence: 90%
“…In their study, the localization was achieved by adding a 1D phase‐encoding gradient pulse after the excitation BIR4 pulse, and localized FAST data were acquired in 17–39 min (PCr‐to‐ATP exchange only) at 1.5 T . In a 3D‐TSE (turbo spin echo) imaging study of calf muscles at 7 T, Parasoglou et al used continuous ST and IR to measure the PCr‐to‐ATP exchange rates of the gastrocnemius muscle (0.31 ± 0.05 s −1 ) in 60 min . The P i ‐to‐ATP chemical exchange rate constant measured in the gastrocnemius muscle by Parasoglou et al in a different 31 P‐MR imaging experiment at 7 T was 0.11 ± 0.04 s −1 .…”
Section: Discussionmentioning
confidence: 99%
“…These simulations are corroborated by the results in skeletal muscle. For both 3T and 7T experiments, the average knormalfCK agrees with the literature measurements that span 0.23 s −1 to 0.35 s −?1 (or 0.459 s −1 if inversion transfer is included ). At 3T, despite the low variation in flip angle, the SNR is relatively low compared to 7T and a correspondingly high estimated CRLB, and high intervoxel variance of knormalfCK is observed.…”
Section: Discussionsupporting
confidence: 86%
“…Since changes in PCr and P i during a perturbation protocol are closely associated with mitochondrial function, these two metabolites are frequently the focus of spectrally selective 31 P imaging studies. To select the metabolite of interest (e.g., PCr) for imaging, a frequency-selective excitation pulse can be used without the presence of a slice-selective gradient (147,148). The subsequent image acquisition using phaseand frequency-encoding gradients is similar to that of 1 H…”
Section: Spectrally Selective Imaging Methodsmentioning
confidence: 99%
“…An interleaved excitation scheme further enables simultaneous quantification of PCr and P i , which allows the quantification of pH from the phase difference between PCr and P i (156). Furthermore, MT has also been incorporated into this approach to allow the mapping of the CK reaction rate (147,148). Comparing to conventional MRSI methods, imaging techniques using spectrally selective approaches provide the opportunity for improved spatial resolution with reduced imaging time, which enables dynamic metabolic mapping during a perturbation protocol.…”
Section: Spectrally Selective Imaging Methodsmentioning
confidence: 99%